Techno-economic analysis of waste heat recovery on the organic Rankine cycle: A case study at Gunungsitoli gas engine power plant - Imansyah Ibnu Hakim (BKS-TM Indonesia, 2025)
The organic Rankine cycle (ORC) is a technology that can utilize waste heat potential from various sources, including isolated power plants such as gas turbine power plants (PLTMG). The Gunungsitoli Nias PLTMG has a significant opportunity to utilize its waste heat, which is at a temperature of 270°C, through the implementation of an ORC system. A techno-economic analysis is necessary to assess the viability of implementing this concept. In this study, the optimal pressure, mass flow, and temperature parameters for achieving the highest net power were investigated. The ORC simulations were conducted using the Aspen HYSYS software to evaluate its performance. There are three variations of test cases: Single ORC (SORC) with R134a, SORC with R245fa, and Dual ORC (DORC) with a dual cycle of R245fa/R134a. An economic analysis was conducted using three methods to assess the feasibility of implementing ORC technology at the PLTMG. The analysis included the Payback Period (PBP), Internal Rate of Return (IRR), Net Present Value (NPV), and Levelized Cost of Energy (LCOE) metrics. The results of the study indicate that the DORC R245fa/R134a system produces the highest net power output with operating parameters of pressure 14/12 Bar, mass flow 0.6/1.1 kg/s, and temperature 154/49 °C, yielding an ORC-R245fa/R134a result of 5,727 Watts/1.703% for the heat source from one unit PLTMGs and 28,595 Watts/1.70% for the heat source from 5 units PLTMG, which is higher than the SORC configuration for each fluid R245fa and R134a. The configuration becomes economically viable when the isentropic efficiency of the expander and pump is changed to 75% and 80%, respectively, and the mechanical efficiency is changed to 95%. The SORC-R245fa configuration yields the most economically advantageous configuration with an IRR of 10.09%, 355.45 million (NPV), 12 years (PP), and 966.54 Rp/kWh (LCOE) for the flue gas source from one units PLTMG, as well as 15.36% (IRR), 2,839.96 million (NPV), 8 years (PP), and 702.52 Rp/kWh (LCOE) for flue gas sources from five units PLTMG.